Metabolism elucidation of BJ-B11 (a heat shock protein 90 inhibitor) by human liver microsomes: identification of main contributing enzymes. (July 2015) - Lu, Danyi; Dong, Dong; Liu, Zhong; Wang, Yifei; Wu, Baojian
<x xml:space="preserve">Abstract</x> Objective: The aim of this article is to elucidate the metabolic pathways of BJ-B11, a heat shock protein 90 inhibitor, in human liver microsomes (HLM) and determine the main enzymes responsible for formation of each metabolite. Methods: Metabolites of BJ-B11 were identified using the ultra performance liquid chromatography- quadrupole time-of-flight/mass spectrometry (UPLC-QTOF/MS) method. Esterase contributing to the hydrolysis of BJ-B11 was identified by chemical inhibition and activity correlation assays. Reaction phenotyping and kinetic studies using expressed cytochrome P450 (CYP) enzymes were performed to determine the contributions of CYP isozymes to BJ-B11 metabolism. Results: BJ-B11 was rapidly hydrolyzed to generate a deacetylated product M1-1. M1-1 was subsequently metabolized to form eight metabolites. Hydrolysis of BJ-B11 was markedly inhibited by vinblastine (a dual inhibitor of arylacetamide deacetylase and carboxylesterase 2). By contrast, digitonin and telmisartan (the specific inhibitors for carboxylesterase 1 and carboxylesterase 2, respectively) did not inhibit BJ-B11 hydrolysis at all. Further, BJ-B11 hydrolysis was significantly correlated with hydrolysis of phenacetin (an activity marker of arylacetamide deacetylase). Moreover, reaction phenotyping revealed that metabolism of M1-1 in HLM was attributable to several CYP enzymes, including CYP1A1, 1B1, 3A4 and 3A5. Conclusion: BJ-B11 was subjected to efficient metabolism in the liver, generating nine metabolites. BJ-B11 metabolism was contributed mainly by arylacetamide deacetylase and multiple CYP enzymes.